Inovative Design of Mattress by Using TRIZ and QFD - Soewardi, Hartomo; Edhi, Ginanjar Sarwo (International Series on Interdisciplinary Science and Technology, 2017)
Abstract–At this time the need for the design of a product is increased. Mattress is a necessity for every individual to rest. Preliminary studies of the function of the mattress stated that the use of the existing mattress found complaints (too large 72%, less attractive 40%, 80% less flexible, less comfortable 40%). Therefore, multifunctional mattress is needed. The purpose of this study is to propose a multifunctional design for a mattress. TRIZ method is used to determine the inventive principles of each attribute and QFD method is used to determine the design parameters of the mattress. Functions that can be developed from a mattress are that it can be folded, it can be a sofa / seating, into the table, flexible /easily removable and as the ironing board. The results of this study shows that the multifunctional mattress design was satisfied the customer feeling and emotion. Keyword–Mattress, TRIZ, QFD, Multifaction, Design